Differences in calcium requirements for B-cell tolerance and immunity. - Desaymard, C; Shinton, R; Waldmann, H (1980)
Incubation of unprimed spleen B cells with high concentrations of hapten-conjugates resulted in the induction of specific unresponsiveness or tolerance to a subsequent encounter with the hapten on a potentially immunogenic carrier. This process of tolerance induction could occur in the absence of extracellular calcium. In contrast B-cell activation to both proliferation and subsequent antibody secretion is known to be calcium dependent. This means that either (1) the decisions which determine immunity and tolerance in B cells are mediated through totally distinct signalling pathways, or that (2) if tolerance and immunity depend on same common signalling events, then the commitment of B cells to switch on or off must be determined at a very early stage.